Keanekaragaman, perilaku kunjungan, dan efektivitas serangga penyerbuk pada tanaman mentimun (Cucumis sativus Linn.) - Phika Ainnadya Hasan; Tri Atmowidi; Sih Kahono (Jurnal Entomologi Indonesia, 2017)
Cucumber is a monoceous plant and require pollinators for pollination process. Diversity and foraging activity of pollinators affect the effectiveness of pollination, which can improve the yields. The aim of this research were to study the diversity, foraging behavior, and effectiveness of insect pollinators on cucumber plants. Scan sampling was used as on of the methodology for observing pollinator diversity, while foraging behavior was observed using focal sampling. Pollination effectiveness were measured based on the number of fruit set of opened and caged plants. Fifteen species were found as pollinator of cucumber, i.e., Xylocopa confusa Pérez, Xylocopa latipes (Drury), Xylocopa caerulea Fabricius, Ceratina bryanti Cockerell, Amegilla burnensis Lieftinck, Nomia quadridentata Bingham, Nomia sp., Megachile unbripennis Smith, Megachile aff. disjuncta Fabricius, Megachile conjuncta Smith, Campsomeris javana Lepeletier, Syrphus sp., Parasyrphus sp., Eurema hecabe Linnaeus, and Vanessa cardui Linnaeus. The longest visit on cucumber flower pattern was by Syrphus sp. (50.71 seconds/flower), while the shortest visit was by X. confusa (4.78 seconds/flower). Pollination by insects increase 100% production as measured by healthy fruit per plant. Pollination also increase 77.61% of seeds number per fruit and 28.57% of seed weight.